2018
DOI: 10.1017/s0021859617000879
|View full text |Cite
|
Sign up to set email alerts
|

Classification of multi-temporal spectral indices for crop type mapping: a case study in Coalville, UK

Abstract: Remote sensing (RS) offers an efficient and reliable means to map features on Earth. Crop type mapping using RS at various temporal and spatial resolutions plays an important role spanning from environmental to economical. The main objective of the current study was to evaluate the significance of optical data in a multi-temporal crop type classification-based on very high spatial resolution and high spatial resolution imagery. With this aim, three images from WorldView-3 and Sentinel-2 were acquired over Coal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 55 publications
1
32
0
7
Order By: Relevance
“…Specifically, the Normalized Difference Vegetation Index (NDVI) 12 , Soil-Adjusted Vegetation Index (SAVI) 13 and Enhanced Vegetation Index (EVI) 14 have been used for monitoring vegetation systems or ecological responses to environmental change 15 . MSI data have been used for identifying crop types [16][17][18] , plastic-covered greenhouses 19 , water bodies 20 and some previous studies showed the potential of VIs calculated from MSI data. However, it is possible to calculate a vast number of VIs from MSI data and most of them have been ignored in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the Normalized Difference Vegetation Index (NDVI) 12 , Soil-Adjusted Vegetation Index (SAVI) 13 and Enhanced Vegetation Index (EVI) 14 have been used for monitoring vegetation systems or ecological responses to environmental change 15 . MSI data have been used for identifying crop types [16][17][18] , plastic-covered greenhouses 19 , water bodies 20 and some previous studies showed the potential of VIs calculated from MSI data. However, it is possible to calculate a vast number of VIs from MSI data and most of them have been ignored in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate land cover assessments form the basis for such analyses in agricultural areas [14], and are particularly important for planning of water resources [15], automated short-term monitoring for yield estimation [16], sustainable land management [17], crop modeling before the end of season [18], or plot extraction for high-throughput phenotyping [19][20][21]. Further, current conditions and extent of land cover are needed as a basis for climate change modeling [22].…”
Section: Introductionmentioning
confidence: 99%
“…Multispectral satellite data, e.g., stemming from RapidEye [35], SPOT 5 [36], QuickBird MS [16], IKONOS [16,37], WorldView-2 [38], or WorldView-3 [14], have been widely used to assess land cover in agricultural areas. These datasets have typical spatial resolutions between 0.5 m-6.5 m, and varying spectral bands (in terms of number, center wavelength and band width) mainly in the visible (VIS) and near-infrared (NIR) spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…The national grassland frequency map addresses these limitations and improves knowledge about semi-natural grasslands in two ways. First, its 250 m resolution identifies semi-natural grasslands more accurately than maps produced from LPIS or CORINE Land Cover at a spatial resolution of 5 km [22] or from the EVA database at a spatial resolution of 10 km [19]; second, it uses long-term monitoring to discriminate between semi-natural and temporary grasslands, which is something that LULC maps derived from annual time-series analysis of remote sensing data do not do [23,25,30].…”
Section: Can a Decadal Modis 250 M Time-series Identify Semi-natural mentioning
confidence: 99%
“…Beyond these broad-scale maps based on the CORINE Land Cover layer, many studies based on automatic and fine-scale analyses have demonstrated the contribution of multi-temporal and high-spatial-resolution satellite data in discriminating grasslands from other LULC types [16,[23][24][25], characterizing forage quality [20], identifying agricultural practices [26] and mapping floristic variation in semi-natural grasslands [27][28][29]. However, discriminating semi-natural and temporary grasslands accurately remains a concern [23,30] due to the lack of temporal depth in remote sensing time-series and because a one-year observation is insufficient to discriminate between semi-natural and temporary grasslands [31]. For instance, the French national land use map as well as the European high-resolution layer (HRL) for "grassland", both derived from multi-temporal Sentinel and Landsat data, combine semi-natural and temporary grasslands into a single "grassland" class.…”
Section: Introductionmentioning
confidence: 99%